Thyroid dose assessments due to inhalation of 131I for nuclear medicine workers - Liu, Gang; Li, Ye; Zhang, HanYu; Zhang, Xue; Liu, Yin Yin; Wu, Xiao Qin; Niu, Li Mei; Zhang, Rong (Frontiers in Public Health, 2022)
Background: In general, medical staff who worked in nuclear medicine should be entirely safe in their professional environment. Nevertheless, we already know that the working environment of the nuclear medicine staff is not completely safe, due to the handling of high amounts of radionuclides for diagnostic and therapy applications which is especially relevant for 131I (as non-sealed source). Purpose: Assessment of inhaled 131I thyroid dose in nuclear medicine workers and introduction of a simple method for internal exposure monitoring. Methods: Using 2-IN *2-in NaI (Tl) scintillation spectrometer and its supporting software (InSpector Maintenance Utility and Genie 2000), from 2019 to 2021,internal thyroid irradiation monitoring, An internal thyroid irradiation monitoring investi A NaI (Tl) scintillation spectrometer and its sugation was carried out for three consecutive years, between 2019 and 2021, in staff members of nuclear medicine departments engaged with iodine therapy. Results: 131I activity was found highest in the thyroid of nuclear medicine workers involved with the manual packaging and delivery of the radioisotope, while it was not detected in staff members involved with the automatic packaging and drug delivery.The activity range was found to be 30.00 ± 6.60—6070.00 ± 1335.40 Bq for the exposed personnel, the estimated dose was 0.05-6.77mSv. In 2021, three workers had an annual equivalent dose above 5 mSv. Conclusion: By monitoring the thyroid 131I in staff members of the nuclear medicine department, it was found that there are 131I internal exposure occupational risks. The automatic packaging and drug delivery is the best solution.